High-performance work system based on the AMO model, knowledge sharing, and employee performance in Vietnam’s private firms - Duong, Thi Hoai Nhung; Le, Thai Phong; Le, Ba Phong; Lusk, Benedicta (Journal of International Economics and Management, 2024)
This study investigates the relationship between knowledge sharing and high-performance work systems (HPWS) using the ability, motivation, and opportunity (AMO) framework. It is presumed that AMO-enhancing practices encourage knowledge sharing among staff members. Additionally, this research focuses on the impact of knowledge sharing on employee performance. The data were obtained from 260 employees and 79 line managers in 26 private Vietnamese companies. Exploratory and confirmatory factor analyses were conducted to verify the data, and structural equation modeling was used to evaluate the hypotheses. The results show that the HPWS is positively related to knowledge sharing. Opportunity-enhancing practices have the greatest impact on employees’ knowledge sharing, whereas motivation-enhancing practices have the least effect. These findings provide a strong basis for improving employee performance by stimulating knowledge sharing among organizational employees. This study also contributes to the literature by employing knowledge sharing to explore the connection between HPWS and employee performance in the private sector.